Near-infrared spectroscopy measured cerebral oxygenation in full-term infants during transition: an observational study - Marwa Mohamed Farag; Hesham Abd E. L.-Rahim Ghazal; Alaa Ibrahim; Bahaa Hammad (SpringerOpen, 2022)
Abstract Background Brain is one of the most sensitive organs to hypoxia during resuscitation. NIRS-measured cerebral oxygenation is an evolving brain monitoring tool for neonatal resuscitation. Methods We undertook a prospective observational study for monitoring of cerebral oxygenation and peripheral preductal saturation at 1, 5, and 10 min after birth. Fractional tissue oxygen extraction was calculated as well. In addition to studying factors affecting cerebral oxygenation at those points in time. For the current cohort, cerebral oxygenation centile charts were provided at those time points. This work was registered in the cinicaltrial.gov NCT05158881. Results Sixty healthy term neonates were enrolled to define reference ranges and centile charts of cerebral oxygenation at 1, 5, and 10 min after birth. The strongest correlations between cerebral oxygenation metrics and peripheral preductal saturation were at 5 min after birth with r value = 0.628. Using logistic regression analysis to determine the most significant factors affecting NIRS-measured crSO2 in healthy full-term neonates, we found that the mode of delivery was the most significant factor with OR = 4.000 (1.367-11.703) at 5 min and 8.726 (2.517-30.25) at 10 min. Conclusions Normal values for NIRS may help to identify infants with cerebral oxygenation below a certain value indicating regional hypoxia at certain time points and can guide neonatal resuscitation interventions. Caesarean section is the most significant factor affecting cerebral oxygenation during the transition of healthy full-term neonates.